Data of Psychosocial, oral health conditions, oral health behaviours in patients with a facial burn injury - Chaudhary, Farooq Ahmad (2020)
Psychosocial distress and oral health status in patients with facial burns. Thesis: Farooq Ahmad Chaudhary, 2020. Data shows the mediation of oral health behaviours in the relationship between psychosocial distress and oral health conditions. It included psychometric (OHIP-14, HADS, SWAP, BRS, RSES, MSPSS), clinical (DMFT, CPI, OHI-S, oral health status derived from the three clinical variables), health behaviours and sociodemographic measures used in the report "The relationship between psychosocial distress and oral health status in patients with facial burns and mediation by oral health behaviour."